Effects of dexmedetomidine on inflammatory responses in patients undergoing laparoscopic cholecystectomy. Issue 4 (14th December 2012) - KANG, S.‐H.; KIM, Y.‐S.; HONG, T.‐H.; CHAE, M.‐S.; CHO, M.‐L.; HER, Y.‐M.; LEE, J.
<x xml:space="preserve">Abstract</x> Background Dexmedetomidine has been shown to reduce pro‐inflammatory cytokine levels in rats with sepsis and in severely ill patients. The aim of this study was to document the effects of dexmedetomidine on inflammatory responses during and after surgery. Materials and Methods Patients undergoing laparoscopic cholecystectomy were enrolled. After induction of anaesthesia, patients in the dexmedetomidine group (n = 24, group D) received a loading dose of dexmedetomidine (1.0 μg/kg), followed by infusion of dexmedetomidine at 0.5 μg/kg/h. A saline‐treated group (n = 23, group S) served as a control. Intraoperative mean arterial pressure (MAP), heart rate (HR), and amount of rescue analgesic administered as post‐anaesthetic care were compared between the groups. The pro‐inflammatory cytokines tumour necrosis factor (TNF)‐α, interleukin (IL)‐1β, and IL‐6, and anti‐inflammatory cytokines IL‐4 and IL‐10 were quantified by sandwich enzyme‐linked immunoassay at three times: after anaesthesia induction (T0), at the end of peritoneal closure (T1), and 60 min after surgery (T2). The C‐reactive protein (CRP) level and leukocyte count were measured on post‐operative day 1. Results At time points T1 and T2, the IL‐1β, TNF‐α, and IL‐10 levels were lower in group D than in group S (P < 0.05). The CRP level and leukocyte count on post‐operative day 1 were also lower in group D (P < 0.05), as were intraoperative MAP, HR, and amount of rescue analgesic administered after surgery. Conclusions Dexmedetomidine administration during surgery reduced intraoperative and post‐operative secretion of cytokines, as well as post‐operative leukocyte count and CRP level.